2005
DOI: 10.1002/adfm.200500042
|View full text |Cite
|
Sign up to set email alerts
|

Ultrarapid Engineering of Biomimetic Materials and Tissues: Fabrication of Nano‐ and Microstructures by Plastic Compression

Abstract: Currently, the concept of engineered tissues depends on the ability of cultured cells to fabricate new tissue around a scaffold. This is inherently slow and expensive and has had limited success so far. We report here a new process for the cell‐independent, controlled engineering of biomimetic scaffolds by rapid removal of fluid from hyperhydrated collagen gel (or other) constructs, using plastic compression (PC). PC fabrication produces dense, cellular, mechanically strong native collagen structures with cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
517
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 426 publications
(534 citation statements)
references
References 23 publications
10
517
1
Order By: Relevance
“…Central in this concept is the reduction of the liquid content of the scaffold, which is a result of the casting. 21 Plastic compression therefore yields scaffolds much denser than conventional, uncompressed collagen type I matrices. The moduli of these conventional scaffolds are typically below 1 kPa, 22,23 and these scaffolds should first grow stronger in culture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Central in this concept is the reduction of the liquid content of the scaffold, which is a result of the casting. 21 Plastic compression therefore yields scaffolds much denser than conventional, uncompressed collagen type I matrices. The moduli of these conventional scaffolds are typically below 1 kPa, 22,23 and these scaffolds should first grow stronger in culture.…”
Section: Discussionmentioning
confidence: 99%
“…18 In this study, we used a plastic compression technique to develop collagen I-based scaffolds with varying concentrations and viscoelastic properties. This is a novel technique that was first described by Brown et al 21 as a form of cell-independent engineering. Central in this concept is the reduction of the liquid content of the scaffold, which is a result of the casting.…”
Section: Discussionmentioning
confidence: 99%
“…While hydrogel stiffness depends on factors such as its concentration and cross-linking, due to its nonlinear behaviour, the stiffness can be altered as a result of internal contractile forces exerted by cells or by another internal compressing and/or stretching forces exerted within it [1,2]. Several approaches have been proposed in the literature to enhance the local stiffness of the hydrogel, including plastic compression [6], cross-linking techniques [3] and magnetic field alignment of collagen-based hydrogels [1]. A helpful alternative approach to remotely induce an internal force within hydrogels and to change their relative local stiffness is to incorporate magnetic nanoparticles within them.…”
Section: Introductionmentioning
confidence: 99%
“…Fibrinencapsulated keratinocytes applied to the surface of Alloderm produce a continuous epithelium with a cornified layer and basement membrane after 4 weeks in vivo (Bannasch et al 2008). Brown et al (2005) and co-workers have shown that plastic compressed collagen gel can be used to encapsulate fibroblasts for tissue engineering the dermis. The compression was only seen to reduce cell viability of encapsulated human dermal fibroblasts by 10% as long as the gel did not become desiccated.…”
Section: Skinmentioning
confidence: 99%